Bipolar circumcision: A new technique for an old procedure with quantified cosmetic outcome - Naser El-Mefleh; Mahmoud Kaddah; Muhammad Eyad Ba'Ath (Wolters Kluwer Medknow Publications, 2021)
Background: Circumcision using bipolar diathermy is well established and used widely. It seems to be superior in terms of post operative complications. The cosmetic outcome of the procedure has never been quantitatively described though. Aims: To describe a modification to performing circumcision with bipolar that involves applying four clamps to the foreskin as it is being amputated with the bipolar so that a consistent length of the mucosal cuff can be obtained with a single almost bloodless cut. Methods: Prospective case series of all patients circumcised using the 4 clamps traction and bipolar cut technique. The cosmetic outcome was assessed in terms of the length of the mucosal cuff in absolute numbers and in proportion to the penile and glanular length. Results: Seventy four patients were recruited with a median age of 3.5 months. No complications were encountered. The average length of the penis was 40 ± 13 mm and the glans 12 ± 3.6 mm. The average length of the mucosal cuff was 8.4 ± 2.9 mm, and the proportion to total penile length was 21.1% ± 4.7% and to glans length 72% ± 24.1%. Conclusion: The four clamp traction method with bipolar circumcision is safe and has a satisfactory cosmetic outcome.